2012
DOI: 10.1164/rccm.201104-0717oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Endothelial Ca2+ and Permeability Response to Platelet-Activating Factor Is Mediated by Acid Sphingomyelinase and Transient Receptor Potential Classical 6

Abstract: The present findings outline a new signaling cascade in the induction of PAF-induced lung edema, in that stimulation of ASM causes recruitment of TRPC6 channels to caveolae, thus allowing for Ca(2+) influx and subsequent increases in endothelial permeability that are amplified in the absence of endothelial NO synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 47 publications
8
65
0
1
Order By: Relevance
“…Recent studies have shown that TRPC6 plays a key role in the onset of the lung ischemia-reperfusion edema (LIRE) as a consequence of endothelial NOX2-dependent ROS, which, in turns, leads to PLCγ activation, DAG kinase inhibition and an increase in submembranal DAG levels [250] . Consistently, PAF-induced lung edema depends upon the activation of acid sphingomyelinase (ASM), which engages TRPC6 to caveolae, thereby resulting in Ca 2+ influx and following increase in endothelial permeability [251] . This process is inhibited by NO donors [251] .…”
Section: Moccia F Et Al Camentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that TRPC6 plays a key role in the onset of the lung ischemia-reperfusion edema (LIRE) as a consequence of endothelial NOX2-dependent ROS, which, in turns, leads to PLCγ activation, DAG kinase inhibition and an increase in submembranal DAG levels [250] . Consistently, PAF-induced lung edema depends upon the activation of acid sphingomyelinase (ASM), which engages TRPC6 to caveolae, thereby resulting in Ca 2+ influx and following increase in endothelial permeability [251] . This process is inhibited by NO donors [251] .…”
Section: Moccia F Et Al Camentioning
confidence: 99%
“…Consistently, PAF-induced lung edema depends upon the activation of acid sphingomyelinase (ASM), which engages TRPC6 to caveolae, thereby resulting in Ca 2+ influx and following increase in endothelial permeability [251] . This process is inhibited by NO donors [251] . TRPC4/5: TRPC4 and TRPC5 form a subfamily with the closest homology with TRPC1 [201] .…”
Section: Moccia F Et Al Camentioning
confidence: 99%
“…In the lung, dysregulated TRPC6 activity may contribute to pulmonary hypertension (Yu et al, 2009;Smith et al, 2015), allergic airway disease (Sel et al, 2008), and ischemia/ reperfusion-associated edema (Weissmann et al, 2012) or permeability-type barrier failure (Samapati et al, 2012). In the kidney, familial forms of focal segmental glomerulosclerosis are a prominent phenotype that can be caused by gain-of-function mutations in the TRPC6 gene or by TRPC6 overexpression (Winn et al, 2005;Krall et al, 2010).…”
Section: Larixyl Acetate Is a Trpc6 Inhibitormentioning
confidence: 99%
“…TRPC6 is expressed in vascular and airway smooth muscle cells (Welsh et al, 2002;Dietrich et al, 2006;Wang and Zheng, 2011) and contributes to the vasoconstrictor response either by mediating receptorand second messenger-triggered Ca 21 influx, or by depolarizing the smooth muscle cell, resulting in the opening of voltagegated Ca 21 channels. In the pulmonary vascular system, TRPC6 has gained considerable attention from several studies that demonstrated its involvement in hypoxia-induced pulmonary vasoconstriction (HPV) (Weissmann et al, 2006;Fuchs et al, 2011;Tabeling et al, 2015) and idiopathic pulmonary hypertension (Yu et al, 2004(Yu et al, , 2009, and also its role in contributing to lung edema formation (Samapati et al, 2012;Weissmann et al, 2012). In addition, TRPC6 expression in lung macrophages (Finney-Hayward et al, 2010) and in bronchial smooth muscle cells may provide a link between TRPC6 and pathophysiological mechanisms that induce or aggravate chronic or allergic obstructive airway diseases (Sel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Platelet-PMN and endothelial-PMN costimulation may not only be promoted by PMPs, but likewise by PMN microparticles (NMPs), since endotoxin (LPS) can stimulate adherent PMNs to release NMPs that generate platelet-activating factor (PAF), thus causing activation of platelets (172), endothelium (149), and other inflammatory cells. In the air spaces, NMPs may also trigger inflammatory responses and epithelial cell damage, as suggested from their abundance in sputum from patients with cystic fibrosis (136).…”
Section: Potential Detrimental Effects Of Microparticles In Alimentioning
confidence: 99%